Organizational knowledge and capabilities in healthcare: Deconstructing and integrating diverse perspectives. (2nd June 2017) - Evans, Jenna M; Brown, Adalsteinn; Baker, G Ross
Diverse concepts and bodies of work exist in the academic literature to guide research and practice on organizational knowledge and capabilities. However, these concepts have largely developed in parallel with minimal cross-fertilization, particularly in the healthcare domain. This contributes to confusion regarding conceptual boundaries and relationships, and to a lack of application of potentially useful evidence. The aim of this article is to assess three concepts associated with organizational knowledge content—intellectual capital, organizational core competencies, and dynamic capabilities—and to propose an agenda for future research. We conducted a literature review to identify and synthesize papers that apply the concepts of intellectual capital, organizational core competencies, and dynamic capabilities in healthcare settings. We explore the meaning of these concepts, summarize and critique associated healthcare research, and propose a high-level framework for conceptualizing how the concepts are related to each other. To support application of the concepts in practice, we conducted a case study of a healthcare organization. Through document review and interviews with current and former leaders, we identify and describe the organization's intellectual capital, organizational core competencies, and dynamic capabilities. The review demonstrates that efforts to identify, understand, and improve organizational knowledge have been limited in health services research. In the literature on healthcare, we identified 38 papers on intellectual capital, 4 on core competencies, and 5 on dynamic capabilities. We link these disparate fields of inquiry by conceptualizing the three concepts as distinct, but overlapping concepts influenced by broader organizational learning and knowledge management processes. To aid healthcare researchers in studying and applying a knowledge-based view of organizational performance, we propose an agenda for future research involving longitudinal comparative case studies.